Determination of foaming properties in surfactant solutions - Параска, Ольга Анатоліївна; Карван, Світлана Анатоліївна; Рак, Тетяна Сергіївна (Eastern-European Journal of Enterprise Technologies, 2014)
The process of binary surfactant mixture foaming was investigated on the basis of a comprehensive determination of its physicochemical and processing characteristics. Based on the research results, the quantitative characteristics of the foaming of binary surfactant mixtures were determined. The optimum ratio of mixture components and working concentrations of solutions for the efficient application in various product treatment processes was determined. The optimum ratio of the omero-16/LAS-80 surfactant mixture components, which is 33/67 %, for the efficient use in the processes of cleaning and finishing of products, was determined. It was found that for the efficient use in the automatic washing of products, it is not recommended to exceed the working concentrations of the proposed surfactants in the range from 1 to 2 g/l, since the foam increase during materials washing will complicate the removing of the washing residues during the next rinsing. The performance properties (stiffness, indelibility) of polyester and cotton materials after the treatment with the surfactant mixtures were evaluated. The studies have shown that after treating the fabrics with the mixture 80 omero-16/LAS, the material surface becomes softer, which recommends applying the surfactant mixture in the creation of softeners and conditioners for textile products.